Sociología y política, el debate clásico y contemporáneo - Zabludovsky, Gina. (México : Facultad de Ciencias Políticas y Sociales de la UNAM : Grupo Editorial M.A. Porrúa, 1995)
"Noteworthy contribution reflects on central problems of contemporary and classical theory and attempts to bridge European/US and Mexican thought. Addresses democracy and implications of globalization on social theory. Includes an imaginary dialogue between De Tocqueville and Lorenzo de Zavala, an analysis of challenges to the discipline using Gidden's 'radicalized modernity' concept, and a diagnostic of sociology in Mexico"--Handbook of Latin American Studies, v. 57.
Incluye referencias bibliográficas.
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto June 08, 2015).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Sociología política.; Participación política -- México.; Democracia; Political sociology; Political participation -- Mexico; Democracy; Libros electrónicos.